Local Technical Agroclimatic Committees-Putting tailored climate information in the hands of farmers - Martínez Barón, Deissy; Navarro-Racines, Carlos Eduardo; Sarruf Romero, Lauren P. (2019)
Local Technical Agroclimatic Committees (LTACs) have become essential tools for farmers in Latin America to manage their crops according to climate conditions. LTACs provide a space for designing and implementing effective actions to reduce agroclimatic risk in agriculture for diverse stakeholders, such as decision-makers, the private sector, academic institutions, scientists, and most importantly, farmers.